Differential Expression of lncRNAs in Ovarian Tissue of Meigu Goats During the Sexually Immature and Mature Periods - Juntao Li; Yanan Xue; Tao Zhong; Linjie Wang; Li Li; Hongping Zhang; Siyuan Zhan (Current Issues in Molecular Biology)
The ovary is the primary reproductive organ in goats, and its development significantly influences the sexual maturity and reproductive capacity of individuals. Long non-coding RNAs (lncRNAs) are integral to a wide array of biological processes. However, the regulatory function of lncRNAs in the development of ovarian tissue during sexual maturity in goats remains largely unexplored. In this study, we conducted RNA sequencing on ovarian tissue samples from Meigu goats at sexually immature (3 months, n = 3) and sexually mature periods (6 months, n = 3). We identified a total of 966 lncRNAs across six libraries, with 95 lncRNAs exhibiting differential expression. Additionally, we identified the target genes of these DElncRNAs. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses indicated that these target genes were associated with various biological processes and pathways pertinent to ovarian development, including reproduction, reproductive process, JAK-STAT signaling pathway, progesterone-mediated oocyte maturation, Wnt signaling pathway, and cytokine–cytokine receptor interaction. Furthermore, lncRNA–mRNA interaction network analysis suggested that MSTRG.15120.9 and MSTRG.15110.2 play crucial regulatory roles in ovarian development. This study provides a valuable resource for elucidating the molecular regulatory mechanisms of lncRNAs in ovarian tissue during the sexual maturity period in goats.